Building Educational Resilience: Post-Crisis Management Strategies and Psychosocial Support Systems at Gazi University Partner Schools - Alperen Uslu; Nisa Arslan (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
This study aims to explore post-crisis management strategies and the effectiveness of psychosocial support systems in Gazi University partner schools following the 2023 earthquake disaster. Employing a qualitative approach with a descriptive case study design, the research involved school principals, guidance counselors (PDR), and administrative staff as participants through purposeful sampling techniques. Data were collected via semi-structured interviews, focus group discussions (FGD), and an analysis of crisis protocol documents. The results indicate that educational resilience is constructed through a three-layered intervention model encompassing emergency logistical aid, initial psychosocial support, and long-term clinical monitoring provided by Gazi University's SOHMER unit. Key findings underscore that the transition from administrative leadership to agile operational leadership, combined with the implementation of institutional perception management, is crucial in restoring teachers' emotional commitment and instructional stability. The synergy between the university and its partner schools creates a resilience ecosystem capable of mitigating the secondary impacts of crises on the educational community.